2022
DOI: 10.3390/ijms23073612
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism in Aging and Age-Related Diseases

Abstract: Iron is a trace metal element necessary to maintain life and is also involved in a variety of biological processes. Aging refers to the natural life process in which the physiological functions of the various systems, organs, and tissues decline, affected by genetic and environmental factors. Therefore, it is imperative to investigate the relationship between iron metabolism and aging-related diseases, including neurodegenerative diseases. During aging, the accumulation of nonheme iron destroys the stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 155 publications
(172 reference statements)
1
27
0
1
Order By: Relevance
“…It has been reported that the translation of the APP is regulated by cellular iron levels (Peng et al, 2021). α-secretase and β-secretase activation is particularly critical to attenuate or increase the formation of Aβ and its accumulation in the brain (Tian et al, 2022). The process is regulated by furin, whose transcription is regulated by intracellular iron concentration.…”
Section: Iron Metabolism and Alzheimer's Diseasementioning
confidence: 99%
“…It has been reported that the translation of the APP is regulated by cellular iron levels (Peng et al, 2021). α-secretase and β-secretase activation is particularly critical to attenuate or increase the formation of Aβ and its accumulation in the brain (Tian et al, 2022). The process is regulated by furin, whose transcription is regulated by intracellular iron concentration.…”
Section: Iron Metabolism and Alzheimer's Diseasementioning
confidence: 99%
“…The mobilization of intracellular labile iron pools is one of the major determinants of ferroptosis. 7,[41][42][43] Ferritin can protect cells from ironinduced oxidative stress by buffering LIP. However, iron sequestered in the ferritin shells may become prooxidant in a chronic overexpression process of ferritin and finally lead to ferroptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The iron‐containing transferrin binds to transferrin receptor 1 on the membrane of the cell and is then internalized via endocytosis. The mobilization of intracellular labile iron pools is one of the major determinants of ferroptosis 7,41–43 . Ferritin can protect cells from iron‐induced oxidative stress by buffering LIP.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistent results could reflect different responses of ferritin production under different illness states and at different ages since serum ferritin (47,52) and brain iron and ferritin content increase with aging (53)(54)(55)(56)(57), rendering elderly patients with psychiatric disorders vulnerable to oxidative damage (58), ferroptosis (59) and mortality (60) during severe COVID- 19.…”
Section: Introductionmentioning
confidence: 99%